Long‐tenured independent directors and firm performance - Bonini, Stefano; Deng, Justin; Ferrari, Mascia; John, Kose; Ross, David Gaddis (Strategic Management Journal, 2022)
Abstract Research Summary Agency perspectives suggest long‐tenured independent directors (LTIDs) may be cronies of the CEO, making their boards less effective, but we theorize that LTIDs may have particular expertise and motivation to improve board effectiveness and ultimately firm performance. We find strong support for this prediction using 15 years of data on the S&P 1,500 firms and an instrument based on director age at time of hire. We also find that an LTID adds more value to firms that are complex or mature, had more CEOs during the LTID's tenure, and have less entrenched management. Post hoc analyses of director deaths and shareholder class action lawsuits and activist motions provide additional evidence that LTIDs add value to the firms on whose boards they serve. Managerial Summary We study whether having a long‐tenured independent director (LTID) on the board has implications for firm performance. In general, we find that firms with an LTID perform better than firms without one. The performance benefits accrue primarily to firms that have complex operations, are in the mature stage of their lifecycle, and had more CEOs during the LTID's tenure. That said, firms with entrenched management do not benefit from having an LTID. We also find that firms with an LTID experience fewer class action lawsuits and shareholder activist motions and that the stock market reacts adversely to the death of an LTID. Overall, the evidence is that LTIDs offer valuable experience and stability to the firms on whose boards they serve.